Persepsi terhadap Beban Kerja pada Dosen dengan Tugas Tambahan Perception of Workload on Lecturers with Additional Tasks - ardalepa, nurdin; Hairina, Yulia; Komalasari, Shanty (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
AbstractLecturers are professionals and scientists with the main task of transforming, developing, and disseminating science, technology, and art through research, education, and of course community service. One of the efforts to improve the ability of lecturers is to pay attention to their workload. The workload received by the individual can produce pressure that is manifested under certain conditions. Preliminary studies conducted by the author, namely lecturers with additional tasks who received assignments regarding optimizing the Tri Dharma of higher education also turned out to be charged with administrative affairs of institutions, coupled with human resource problems. The research used is a qualitative type with a case study approach. The subject is a lecturer with additional assignments at the Islamic Psychology Study Program, Faculty of Ushuluddin and Humanities UIN Antasari Banjarmasin. Data collection techniques using interview techniques. The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results of the study obtained different perceptions of the workload of 4 subjects.